Aspects related with physical exercise dependence in university students - Reche-García, C.; Ortín Montero, F. J.; Martínez-Rodríguez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of the current study was to determine the predominance of symptoms of physical exercise dependence in university students and its relationship with variables such as, dedication to practicing sport, trait anxiety, mood, quality of sleep and adherence to a low fat diet. A total of 240 athletes were evaluated, (age: M = 21.1, SD = 4.2). The results showed that 6% have a risk of exercise dependence and was higher in the following cases: women, students below the age of 20, those who practice more weekly sessions and more sport experienced students. The risk of exercise dependence seems to be related with a higher frequency of weekly training sessions, mood alterations, sleep problems, anxious tendency and lower adherence to a low fat diet. These results show psychological indicators and signs of exercise dependence disorder that are evaluable by a sport psychologist for an early detection and intervention.